The Treatment of Advanced Lung Cancer in the Elderly. Issue 5 (September 2015) - Presley, Carolyn; Lilenbaum, Rogerio
<x xml:space="preserve">Abstract</x> Abstract The US lung cancer population is aging, the majority of which receive a diagnosis of incurable advanced non–small cell lung cancer (NSCLC). In US clinical oncology practice, elderly is defined as patients older than 70 years. Treatment of elderly patients with advanced NSCLC is complex. Choosing appropriate chemotherapy in this setting is complicated by multiple chronic conditions in addition to geriatric syndromes, challenging the traditional oncology practice. Although promising new options are on the horizon, the standard of care remains either platinum-based doublet or single-agent chemotherapy. Clinical trials have determined doublet therapy is appropriate for elderly patients; however, out of concern for excessive toxicity, many elderly patients do not receive appropriate treatment. Determining which patients are most likely to benefit from doublet chemotherapy versus monotherapy is a difficult challenge. Researchers have started to implement geriatric assessment and predictive chemotherapy toxicity tools in prospective clinical trials; however, knowledge gaps remain on how to appropriately select and treat elderly patients with advanced NSCLC in efforts to improve disease management and symptoms, maintain functional status, and minimize toxicity.